Asuhan Kebidanan pada Ibu Primi Gravida Usia Remaja di TM II Sebagai Kehamilan Risiko Tinggi: Laporan kasus - Rina Cahya Nurani; Nuryani .; Suparji . (CV. ITTC INDONESIA, 2026)
Introduction: Pregnancy in adolescence (<20 years) is a high-risk pregnancy due to biological and psychosocial immaturity that can increase the risk of maternal and perinatal complications, such as anemia, preeclampsia, preterm labor, and low birth weight babies. This condition requires early detection and comprehensive midwifery care to optimize maternal and fetal health. The purpose of this study is to describe the implementation of comprehensive midwifery care for adolescent primigravida pregnant women in the second trimester with high-risk pregnancies. Methods: Using a design (case report) on Mrs.